Peculiar self‐nucleation behavior of a polybutene‐1/ethylene random copolymer. Issue 5 (31st July 2021) - Wang, Zefan; Dong, Xia; Cavallo, Dario; Wang, Dujin; Müller, Alejandro J.
Abstract: The self‐nucleation behavior of a polybutene‐1/ethylene random copolymer, P(B1‐ ran‐ E), which undergoes a complex crystal‐crystal transition behavior, has been studied in detail. Similar to PE random copolymers, this material shows a strong melt memory effect even above equilibrium melting point of PB‐1 homopolymer. Different polymorphic forms can be obtained when P(B1‐ ran ‐E) is cooled from different self‐nucleation domains. The trigonal form I′ could only be nucleated in the presence of remaining form I crystals via self‐seeding, while the melt memory in Domain IIa could only act as self‐nuclei for kinetically favored form II. Furthermore, observations from optical microscopy illustrated that melt memory is able to enhance nucleation density but it does not affect the spherulitic growth rate. Abstract : The complex self‐nucleation behavior of a polybutene‐1 random copolymer, P(B1‐ ran ‐E), that exhibits polymorphic behavior, is studied in detail. Trigonal form I′ could be obtained when form I crystals were present ( Domain III ), while melt memory induced self‐nuclei ( Domain IIa ) could only promote the nucleation of kinetically favored form II. Optical microscopy results indicate that melt memory can only enhance nucleation density but it cannot affect spherulitic growth rate.